Caracterización del lactosuero en las microempresas productoras de lácteos en la parroquia Mulaló del cantón Latacunga provincia de Cotopaxi. - Guano Velasco, Luis Felipe (2021)
Fresh cheese is the most produced product in the Cotopaxi province, in Mulaló parish; when the whey is improperly disposed of, it generates an environmental problem, because it does not comply with the parameters established in the INEN 2594: 2011 standard, so it is necessary to propose initiatives to industrialize it, optimizing resources and improvements in the management process; performing its physical-chemical and microbiological characterization contributes to this purpose. Whey samples from three representative plants of the study sector were analyzed; Eleven analyzes were carried out in three companies, the analyzes are: physical - chemical made up of: acidity, pH, fat, proteins, total solids, non-fatty solids and microbiological which are: total mesophilic aerobes, total coliforms, e. coli, molds, yeasts. The average results of the analyzed samples have values in the range of serum classification and quality determination based on its composition, a comparison of the results obtained was made, however, they did not present good sanitary quality and safety parameters. The benefits of cheese whey in its composition obtained in the first draining of the cheese, in relation to the averages in total mesophilic aerobes 1 X10 ^ 6 CFU / 1 g or ml - total coliforms 1 X10 ^ 2 CFU / 1 g or ml - e . coli 1 <1 CFU / 1 g or ml - molds 4 X10 CFU / 1 g or ml - yeasts 2 X10 ^ 3 CFU / 1 g or ml, position it as an alternative for use as a culture medium and raw material for biotechnological processes in production of different products in the food industry.